Transparent and attachable ionic communicators based on self-cleanable triboelectric nanogenerators - Younghoon Lee (Nature Portfolio, 2018)
Flexible, transparent wearable electronics harvesting energy from human motion are nearing reality, but stable adhesion while staying clean remains a problem. Here the authors solve both issues with a functionalized organic polymer/hydrogel-based device capable of wireless communication via finger gestures.